Monetary policy effects on bank risk taking - Angela Abbate; Dominik Thaler (National Bank of Belgium, 2015)
Motivated by VAR evidence on the risk-taking channel in the US, we develop a New Keynesian model where low levels of the risk-free rate induce banks to grant credit to riskier borrowers. In the model an agency problem between depositors and equity holders incentivizes banks to take excessive risk. As the real interest rate declines these incentives become stronger and risk taking increases. We estimate the model on US data using Bayesian techniques and assess optimal monetary policy conduct in the estimated model, assuming that the interest rate is the only available instrument. Our results suggest that in a risk taking channel environment, the monetary authority should seek to stabilize the path of the real interest rate, trading off more inflation volatility in exchange for less interest rate and output volatility.
Keywords: E12; E44; E58; 330; Bank Risk; Monetary policy; DSGE Models; Geldpolitik; Bankrisiko; Neoklassische Synthese; DSGE-Modell; USA